Mapping algorithms from QLQ-C30 to EQ-5D utilities: no firm ground to stand on yet. (August 2014) - Crott, Ralph
<x xml:space="preserve">Abstract</x> Aim: Over the last years several mapping or cross-walking algorithms for deriving utilities from QLQ-C30 scores have been published. However their external predictive accuracy has not yet been systematically compared. Methods: We tested the external validity of previously published mapping algorithms to transform the European Organization for Research and Treatment of Cancer QLQ-C30 questionnaire responses to EQ-5D derived Utilities. Results: When applied to different data sets, the currently published mapping showed a large variation between algorithms of the values of the mapped utilities, a low accuracy of the mapping compared to the observed EQ-5D utilities and no consistent performance between competing algorithms. Discussion: Therefore direct mapping from QLQ-C30 profiles to EQ-5D utilities using published algorithms should be viewed cautiously.